Performance of solid particles flow thermal storage material made of desert sand. Issue 15 (3rd August 2018) - Lv, Shuo; Zhu, Guihua; Han, Jinpeng; Wang, Ziyue
ABSTRACT: It is a safe and low-cost new heat storage method to realize sensible heat storage at medium and high temperature by using flowing inorganic inert solid particle materials. The cost and performance of granular heat storage medium are very important for this kind of heat storage technology. The yellow sand in southeast of Tenggri Desert in Ningxia is studied. By thermal shock and grinding methods, the tests of thermal shock-resistance and wear resistance were carried out, under laboratory conditions, for the unscreened raw sand and the screened sand samples with three grain sizes (40–60 mesh, 60–80 mesh, and 80–100 mesh). The particle size of the raw sand is 150–300 µm (60–100 meshes) accounts for 60% (wt %) or more and meets the requirement of heat storage material. The density, thermal conductivity, and specific heat of raw sand are higher than those of three kinds of screened sand. Thermal shock and grinding affect the particle size distribution, density, specific heat, and thermal conductivity of the particles. The degree of influence varies with the particle size. The volume ratio heat capacity is used to measure the heat storage performance of the particles. Thermal shock results in a better thermal storage performance of the screened sand than the original sand. After comprehensive analysis of the properties of three kinds of screened sand, it is found that the content of 60–80 mesh-screened sand (31.75%) is the highest in the original sand. After thermal shock and grinding, the screened sand not only has good heat storage performance (average volumetric specific heat capacity 3.232 J· K −3 · K −1 ), but also has the smallest change of particle size (breaking rate is less than 24, and agglomeration rate is less than 6), and the thermal shock resistance and wear resistance are outstanding. It is suggested that the screened sand with the particle size range of 200-300µm (60–80 mesh), also the particles with the highest content in the original sand, should be selected as the solid particle flowing heat storage medium.